RMPS, religious & philosophical questions - Walker, Joe (Dynamic learning, 2019)
Exam Board: SQA Level: Higher Subject: RMPS First Teaching: August 2018 First Exam: June 2019 The only resource for RMPS Religious and Philosophical Questions at Higher level, written by a bestselling author and expert in the field. Completely updated for the 2018 SQA specification. This book provides comprehensive coverage of the newly designed CFE Higher in Religious, Moral and Philosophical Studies. It is also ideal for students across Scotland studying key topic areas in Religious and Philosophical Questions as part of the broad general education and the senior phase of RME. - Offers a lively, accessible and engaging style with appropriate humour that reflects real-life situations and moral issues - Highlights the importance of dealing with varieties of belief within religious traditions - Deals with up-to-date contemporary and topical issues in a highly sensitive and informative manner.